Menstrual hygiene management among the rural school-going adolescent girls with special emphasis to the Kora tribe in West Bengal, India - Mousumi Ganguly; Sila Jana; Arindam Ganguly; Manasi Chattaraj; Dipak K. Midya (Discover Public Health)
Abstract Aim This study aimed to investigate menstrual practices, awareness, cultural beliefs, and taboos among rural adolescent girls in Bankura, West Bengal, with a special focus on the Kora tribal populations to understand their menstrual hygiene management challenges. Subject and methods A questionnaire-based cross-sectional survey was conducted among 210 participants aged 10–19 years, who were selected through purposive sampling. Results The findings revealed significant gaps in knowledge and practices, with 74.8% of the respondents having no prior understanding of menstruation. Alarmingly, 15.8% perceived menstruation as stigmatizing, leading to restrictions in daily activities and dietary limitations. The study also highlighted the prevalence of homemade reusable pads (75.24%) and inadequate disposal practices (78.57%). Factors such as family income, parental education, and occupation significantly influenced menstrual hygiene practices. This study emphasizes the need for targeted education and intervention to improve menstrual hygiene management among adolescent girls, particularly in rural and underserved communities. Conclusion This study highlights the critical role of socioeconomic conditions and mothers’ education levels in maintaining proper menstrual hygiene among school-going adolescent girls in rural Bankura, West Bengal. Interventions that address these factors are crucial for improving menstrual health and well-being. This study highlights the need for behavior modification programs and advocacy campaigns to address menstrual hygiene management gaps. Recommendations include improving access to water, sanitation, and hygiene infrastructure in schools and promoting gender-neutral facilities to support girls' dignity and well-being.